INVESTIGATING LANGUAGE AND POWER DYNAMICS IN OBAMA'S FAREWELL SPEECH: A CRITICAL DISCOURSE ANALYSIS - Cut Ade Sukma; Fadhlur Rahman (Malikussaleh Social and Political Reviews, 2026)
Every word spoken, every sentence constructed, and every discourse contains ideological weight that reflects the power structures within society. In the political landscape of the United States, presidential speeches hold a special position as a genre of discourse that not only reflects the individual vision of a leader, but also represents the aspirations, values, and identity of the nation. This phenomenon becomes even more significant when analyzed through the lens of critical discourse analysis, which allows researchers to uncover layers of meaning hidden behind linguistic constructions. This study uses critical discourse analysis to examine Barack Obama's farewell speech as a complex discourse practice that reflects and shapes contemporary American socio-political reality. Using Fairclough's three-dimensional analytical framework, this study analyzes the speech in terms of its textual, discursive, and sociocultural dimensions during the contentious transition to the Trump administration. Textual analysis reveals the strategic use of language with carefully chosen vocabulary and grammatical constructions, reinforcing the themes of unity and democracy. At the discourse practice level, the speech employs effective rhetorical strategies, including personal addresses and compelling narratives to build emotional connections with the audience. Sociocultural analysis shows deep integration with the American institutional context, evidenced by the strategic choice of location in Chicago, acknowledgment of racial challenges, and calls to overcome intensifying political polarization. Findings indicate that Obama's farewell speech illustrates how political discourse functions as an instrument for maintaining and transforming democratic values during critical political transitions. The speech's power stems from its sophisticated linguistic construction and its capacity to respond to the broader sociopolitical context with profound nuance.